Restaurant ordering and reservation system / Soo Huey Ling - Soo , Huey Ling (2002)
In order to compete the more demanding business would, the project, Restaurant Ordering and Reservation System is aimed to provide a cost-effective solution for both the restaurant customer and the restaurant/wait staff at a time to provide customer a quality service in a friendly and timely manner. The author had chosen the waterfall model as the development approach. During the development cycle, few techniques to gather information will be applied, namely documentary research, internet surfing, questionnaire and interview. The Restaurant Ordering and Reservation System will be developed using Windows 2000 server, Palm OS 4.0, Parity Software, Appforge and utilizing Micrisoft SQL 7.0 database through. This system will be divided into three parts which are Wireless Handheld Order Taking Syetem, IVR Reservation subsystem and Backend Monitoring susbsystem. An application will be buiilt on a handhled equipped with Palm OS where wait staff can simply take order by touching the screen using stylus pen and the order is then directly send to the kitchen, bar and counter via infrared wireless communication technology. IVR Reservation allows customer make a reservation at any time by phone call. They can use their touch-tone pad to input requests and database will speak information back to the caller. Backend Monitoring is a database that capability to store the customer order taken by the staff wait staff and the reservation information. Since in this country still does not have a company that provides wireless order taking and IVR Reservation solutions, so it is possible that the local market need this technology. It is believed that the Restaurant Ordering and Reservation System will be beneficial to either the customer of the restaurant owner.